Synergetic approach to extracurricular philological education (Pedagogy of Higher and Secondary Education, 2011)
The article deals with the synergy ideas that may be used in the organization of the philological non-formal education. The application of the synergy ideas in teaching and upbringing process will help to harmonize the intellectual and emotional factors in learning, which will finally lead to upbringing a personality able to self-actualization, professional growth and mobility in modern society.
Keywords: non-formal education; type of school; specialization; synergetic approach